Academic Mobility in Teacher Education - V. I. Zagvyazinskiy; L. M. Volosnikova; E. A. Kukuyev; I. V. Patrusheva (Russian State Vocational Pedagogical University, 2020)
Introduction. Nowadays, it is hard to consider higher education of the 21st century without the global context. The increasing globalisation opens up many opportunities for higher education development, while becoming a challenge to national systems for the training of qualified professionals, including teachers. Thus, the internationalisation of teacher education is currently becoming one of the global trends.The aim of the present research was to investigate the state of involvement of future Russian educators in the processes of academic mobility.Methodology and research methods. The research is based on the theory of internationalisation of education in the conditions of increasing globalisation. In the course of the research, the authors used a mixed toolkit: analysis and generalisation of academic publications, statistical data (the Eurostat working papers and OECD's reports) and sociological survey. 1714 students of the universities of Siberia took part in the sociological survey.Results and scientific novelty. The analytical reviews of literature revealed the shortage of academic publications on the problems of internationalisation of pedagogical education and the lack of statistics in the Russian Federation on the academic mobility of future teachers. Based on the results of theoretical analysis, the levels of study of academic migration of students of pedagogical specialties were determined - geopolitical, organisational and personally-oriented. A questionnaire has been developed to ascertain the degree of academic mobility of students. This questionnaire includes scanning the portfolio of respondents, finding out their status and motivation to participate in the internationalisation process and academic exchange programmes. The analysis of the results demonstrates the low level of involvement of students of Siberian universities in the academic mobility programmes against the background of their high degree of readiness to study at other universities, including universities abroad. The reasons for non-involvement are identified.Practical significance. The recommendations for changing the critical situation are proposed. It is highlighted that academic mobility should take an important place in both the curriculum of Russian universalities and the individual educational routes. It is necessary to support academic mobility and form a new teacher's professional identity in the global context.